2022
DOI: 10.1093/lambio/ovac063
|View full text |Cite
|
Sign up to set email alerts
|

Zinc solubilizing Bacillus sp (SS9) and Enterobacter sp (SS7) promote mung bean (Vigna radiata L.) growth, nutrient uptake and physiological profiles

Abstract: Zinc (Zn) is a crucial micronutrient required for optimum plant growth. Zn-solubilizing bacteria (ZSB) are potential alternatives for Zn supplementation and convert applied inorganic Zn to available forms. In this study, ZSB were isolated from the root nodules of wild legumes. From a set of 17 bacteria, the isolates SS9 and SS7 were found to be efficient in tolerating 1 g (w/v) Zn. The isolates were identified as Bacillus sp (SS9, MW642183) and Enterobacter sp (SS7, MW624528) based on morphology and 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Studies have shown that Zn is the specific activation ion of chloroplast carbonic anhydrase, which is a key point in controlling photosynthesis and provides the substrate for CO 2 fixation, thus promoting photosynthesis to a certain extent [62]. At the same time, Zn is a synthesis of chlorophyll precursor zinc porphyrin; thus, Zn is conducive to promoting chlorophyll synthesis, and chlorophyll plays a vital role in photosynthesis [63]. Therefore, it is speculated that the promotion of chlorophyll synthesis by Zn may also be one of the reasons for enhancing photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Zn is the specific activation ion of chloroplast carbonic anhydrase, which is a key point in controlling photosynthesis and provides the substrate for CO 2 fixation, thus promoting photosynthesis to a certain extent [62]. At the same time, Zn is a synthesis of chlorophyll precursor zinc porphyrin; thus, Zn is conducive to promoting chlorophyll synthesis, and chlorophyll plays a vital role in photosynthesis [63]. Therefore, it is speculated that the promotion of chlorophyll synthesis by Zn may also be one of the reasons for enhancing photosynthesis.…”
Section: Discussionmentioning
confidence: 99%